Variable voltage, variable frequency single phase induction motor drive for dumb waiter application - Borjal, Rodel D. (2007)
This project aims to design and construct a variable-frequency motor drive with an output power of 1/2 HP for dumb waiter application. Pulse Width Modulation was utilized to control the input voltage and frequency of the motor. The motor has a load side output frequency range of 30 to 70 Hz, achieved through a mechanical gear system. The lifting mechanism is a simple pulley (with a mounted gearbox, together with a load platform) and a counterweight.
Thesis (B.S. Electronics and Communications Engineering)--University of the Philippines, Diliman.
Keywords: Electric driving, Variable speed; Electric controllers; Electric motors -- Electronic control; Dumb waiter application; Variable frequency motor drive